Teachers Navigating Faith and Inquiry Across Three School Types in Indonesia - Khairil Azhar; Mohammad Ali; Eero Ropo; Juwintar Febriani Arwan (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This study examines how teachers in three types of Indonesian lower secondary schools—a general lower secondary (SMP), a madrasah (MTs), and a traditional pesantren—navigate the tension between cultivating religious faith and fostering critical inquiry. Qualitatively designed, the study employed purposive sampling to select teachers, principals, and vice principals from three school types under a single educational foundation. Data were gathered through focus group discussions and semi-structured interviews, and analyzed thematically to explore how Islamic education is understood and practiced. The findings of this study indicate that Islamic education in Indonesia’s lower secondary schools—across SMP, MTs, and pesantren—is a dynamic and context-sensitive practice shaped by institutional ethos, teacher interpretations, and local socio-cultural realities. The tension between faith and inquiry, a central theme in Islamic educational theory, is not experienced as a binary but negotiated along a continuum. Teachers support questioning to varying degrees, with SMP allowing guided inquiry, MTs placing faith-based boundaries, and pesantren emphasizing critical thinking within Islamic sciences. Integration of religious and secular knowledge also ranges from ethical linkages to philosophical unification, depending on institutional vision and pedagogical approach. Despite challenges, all three school types show selective adaptation to technological, curricular, and societal changes—preserving Islamic values while engaging with contemporary demands. This confirms that Islamic education in Indonesia is an evolving project—shaped by the people, context, and purposes it serves.